Effects of strain and electropulse duration on elastic modulus of TiNi alloy. Issue 11 (23rd July 2020) - Hao, J. Y.; Zhang, G. S.; Shan, W. K.; Li, M.; Li, K. F.; Gong, Z.; Gao, Y. W.; Guo, D. F.
Abstract : The elastic modulus of TiNi alloy was tailored by electroplastic rolling deformation and the effects of rolling strain and electropulse duration on the elastic modulus of electroplastic rolled TiNi alloy were systematically investigated. With rolling strain increasing from 0 to 1.70, the elastic modulus decreases from 61 to 30 GPa, which can be attributed to the increase in dislocation density and deformation-induced low modulus B19 ′ martensite phase. With electropulse duration increasing from 80 to 120 µs, the elastic modulus first decreases due to the volume fraction increase in low modulus B19 ′ martensite phase and then slightly increases on account of the dynamic recovery of dislocation and reverse martensite transformation resulted from electroplastic effect induced by high-energy electropulse.